2023
DOI: 10.1172/jci160456
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 translocation to the plasma membrane enables tumor immune evasion through MIB2 ubiquitination

Abstract: Programmed death-ligand 1 (PD-L1), a critical immune checkpoint ligand, is a transmembrane protein synthesized in the endoplasmic reticulum of tumor cells and transported to the plasma membrane to interact with programmed death 1 (PD-1) expressed on T cell surface. This interaction delivers coinhibitory signals to T cells, thereby suppressing their function and allowing evasion of antitumor immunity. Most companion or complementary diagnostic devices for assessing PD-L1 expression levels in tumor cells used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 64 publications
(73 reference statements)
0
13
0
Order By: Relevance
“…Ding’s team found that sodium-glucose cotransporter 2 (SGLT2) colocalizes with PD-L1 in the cell membrane and circulating endosomes, preventing proteasome-mediated PD-L1 degradation [ 48 ]. Yu et al discovered that MIB E3 ubiquitin protein ligase 2 (MIB2) catalyzes the nonproteolytic K63-linked polyubiquitination of PD-L1, facilitating its transport of PD-L1 from the trans-Golgi network (TGN) to the membrane through RAS-associated binding 8-mediated (RAB8-mediated) exocytosis [ 49 ]. (Fig.…”
Section: Preclinical Study Of Ptms Inhibiting Pd-l1 Expression and Fu...mentioning
confidence: 99%
“…Ding’s team found that sodium-glucose cotransporter 2 (SGLT2) colocalizes with PD-L1 in the cell membrane and circulating endosomes, preventing proteasome-mediated PD-L1 degradation [ 48 ]. Yu et al discovered that MIB E3 ubiquitin protein ligase 2 (MIB2) catalyzes the nonproteolytic K63-linked polyubiquitination of PD-L1, facilitating its transport of PD-L1 from the trans-Golgi network (TGN) to the membrane through RAS-associated binding 8-mediated (RAB8-mediated) exocytosis [ 49 ]. (Fig.…”
Section: Preclinical Study Of Ptms Inhibiting Pd-l1 Expression and Fu...mentioning
confidence: 99%
“…On the one hand, newly synthesized PD-L1 is transported from the Golgi apparatus to membrane. [53] On the other hand, mPD-L1 conducts a series of measures to save itself from degradation. Post-transnational modifications involving ubiquitination, acetylation, and palmitoylation reactions can control mPD-L1's stability and transcriptional activity.…”
Section: Mechanisms For Up-regulation Of Mpd-l1mentioning
confidence: 99%
“…During the whole process, synthesized PD-L1 in the cytosol is transported to the membrane to restore the mPD-L1 pool, thus promoting immune evasion. [53,54] Specifically, newly synthesized PD-L1 is added with k63-linked ubiquitination under the control of mind bomb homolog 2 (MIB2), a type of E3 ligase. Then ubiquitinated PD-L1 translocates from Golgi to the membrane by Ras-associated binding 8-mediated (RAB8-mediated) exocytosis.…”
Section: Mechanisms For Up-regulation Of Mpd-l1mentioning
confidence: 99%
See 1 more Smart Citation
“…PD-L1 tends to internalize after the binding of antibody, during which some of it is lysosome-mediated degradation 8 . However, most of the internalized PD-L1 can be stored in recycling endosomes and repopulated to the cell membrane 9 , mediating resistance to ICI treatment targeting PD-L1 10 , 11 . Therefore, promoting lysosomal degradation and inhibiting the recycling of PD-L1 is a promising approach to overcome the resistance to ICI therapy 12 .…”
Section: Introductionmentioning
confidence: 99%